Analysis of the current state and prospects of development of the Kazakhstan stock market (Journal of Economic Research & Business Administration, 2015)
In this article, was made a detailed analysis of the financial situation of the country and the stock market in particular. Data are presented with statistical reports and the Agency of RK. Were viewed the prospects of theKazakhstan Stock Exchange.
Keywords: Market analysis; development prospects